2014
DOI: 10.1103/physrevlett.112.117401
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Exciton Dissociation in Carbon Nanotubes

Abstract: Simultaneous photoluminescence and photocurrent measurements on individual single-walled carbon nanotubes reveal spontaneous dissociation of excitons into free electron-hole pairs. The correlation of luminescence intensity and photocurrent shows that a significant fraction of excitons are dissociating before recombination. Furthermore, the combination of optical and electrical signals also allows for extraction of the absorption cross section and the oscillator strength. Our observations explain the reasons wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
76
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(85 citation statements)
references
References 32 publications
7
76
0
Order By: Relevance
“…In the SWCNT-C 60 system, wavelength-dependent excitation of different SWCNT bandgaps revealed that the efficiency of charge generation depends sensitively on the free energy driving force for charge separation (ΔG CS ), which trends toward zero at a diameter of ~1.1 nm [16]. Interestingly, that study also revealed that bandgap excitation of neat s-SWCNT films produces a significant yield (~5%) of charge carriers even in the absence of an intentional exciton dissociation interface, in agreement with previous terahertz spectroscopic measurements [17] and recent photocurrent measurements [18].…”
supporting
confidence: 90%
“…In the SWCNT-C 60 system, wavelength-dependent excitation of different SWCNT bandgaps revealed that the efficiency of charge generation depends sensitively on the free energy driving force for charge separation (ΔG CS ), which trends toward zero at a diameter of ~1.1 nm [16]. Interestingly, that study also revealed that bandgap excitation of neat s-SWCNT films produces a significant yield (~5%) of charge carriers even in the absence of an intentional exciton dissociation interface, in agreement with previous terahertz spectroscopic measurements [17] and recent photocurrent measurements [18].…”
supporting
confidence: 90%
“…Indeed, F increases monotonically with S as expected from Eq. (5). We note that the detuning changes sign above and below P = 190 µW, but similar enhancements are obtained for red-(open circles) and blue-detuned (crosses) nanotube emission.…”
supporting
confidence: 77%
“…However, as already discussed above we do not anticipate this effect to be strong for excitons in a confined geometry. Another possibility would be that some of the excitons split into free electron-hole pairs through exciton-exciton collision, leading to much stronger screening 31,35,36 . In the same time, it was predicted that such electron-hole plasma would enhance the reduction of oscillator strength when the temperature is much lower than the exciton binding energy, which is the case for carbon nanotubes 14 .…”
Section: Comparison With Experimentsmentioning
confidence: 99%